Global esophageal cancer epidemiology in 2022 and predictions for 2050: A comprehensive analysis and projections based on GLOBOCAN data - Ling Qi; Mengfei Sun; Weixin Liu; Xuefeng Zhang; Yongjun Yu; Ziqiang Tian; Zhiyu Ni; Rongshou Zheng; Yong Li; Xiangxiang Pan (Chinese Medical Journal)
Abstract. Background:. The burden of esophageal cancer varies across different regions of the world. The aim of this study is to analyze the current burden of esophageal cancer in 185 countries in 2022 and to project the trends up to the year 2050. Methods:. We extracted data on primary esophageal cancer cases and deaths from the GLOBOCAN 2022 database, which includes data from 185 countries. Age-standardized incidence rates (ASIR) and mortality rates (ASMR) per 100,000 person-years were calculated by stratifying by Human Development Index (HDI) levels and regions. Considering changes in population size and age structure, we assumed that the risks of incidence and mortality remain constant at the levels of 2022 to forecast the number of new cases and deaths from esophageal cancer globally by 2050. Results:. In 2022, an estimated 511,054 people were diagnosed with esophageal cancer globally, and 445,391 died from the disease. The global ASIR and ASMR for esophageal cancer were 5.00 and 4.30 per 100,000, respectively. The highest rates were observed in East Africa (7.60 for incidence, 7.20 for mortality per 100,000), East Asia (7.60 for incidence, 5.90 for mortality per 100,000), Southern Africa (6.30 for incidence, 5.90 for mortality per 100,000), and South Central Asia (5.80 for incidence, 5.50 for mortality per 100,000). Among the 185 countries worldwide, esophageal cancer was among the top five causes of cancer incidence in 18 countries and among the top five causes of cancer mortality in 25 countries. In 2022, China had 224,012 new cases and 187,467 deaths from esophageal cancer, accounting for approximately 43.8% and 42.1% of the global total, respectively, which is higher than the proportion of China’s population to the global population (17.9%). ASIR was 8.30 per 100,000, and ASMR was 6.70 per 100,000. The highest burden of esophageal cancer was in high HDI countries, with new cases and deaths accounting for 51.3% and 50.0% of the global total, respectively. The ASIR and ASMR were highest in the high HDI group (6.10 and 5.10 per 100,000, respectively), also exceeding the global averages. There was a trend of decreasing mortality to incidence ratio with increasing HDI, but no correlation was observed between HDI and ASIR or ASMR. In all regions worldwide, the incidence and mortality rates were higher in males than in females (with a male-to-female ASR ratio ranging from 1.10 to 28.7). Compared to 2022, it is projected that by 2050, the number of new esophageal cancer cases will increase by approximately 80.5%, and deaths will increase by 85.4% due to population growth and aging. Conclusions:. The burden of esophageal cancer remains heavy. Adopting a healthy lifestyle, including reducing tobacco and alcohol intake, avoiding moldy foods, and increasing intake of fresh fruits and vegetables, can help reduce the risk of stomach and esophageal cancer. In addition, the development and implementation of evidence-based and effective public health policies are critical to reducing the global disease burden of esophageal cancer.